KEMAMPUAN MENULIS TEKS PROSEDUR PADA SISWA KELAS XI TKJ DI SMK NEGERI 1 BENGKAYANG - Yayuk, Yayuk Sovia; Seli, Sesilia Seli; Sisilya, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine "The Ability to Write Procedure Texts in Class XI TKJ Students at SMK Negeri 1 Bengkayang". The problem in this study is the ability to write procedural texts from the aspect of structure (goals, steps, and closing), linguistic rules (command verbs, technical words, conjunctions, persuasive statements, tool descriptions), and aspects of content accuracy with the type of text. This study uses descriptive statistical methods in quantitative form. The technique that used in data collection is the test technique (in the form of essay questions). The data was analyzed by descriptive statistics. The results of the research on the ability to write procedural texts in class XI TKJ SMK Negeri 1 Bengkayang are in the "enough" category. The average value in the structural aspect is 31.08 in the capable category, the average value in the linguistic rule aspect is 28.66 in the sufficient category, and the average value in the content accuracy aspect with the type of text is 11.52 with the capable category.